2014
DOI: 10.5539/sar.v3n2p89
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions of Beef Cow-Calf Grazing Systems in Uruguay

Abstract: <p>Evaluating greenhouse gas (GHG) emissions at farm level is an important tool to mitigate climate change. Livestock account for 80% of the total GHG emissions in Uruguay, and beef cow-calf systems are possibly the largest contributors. In cow-calf grazing systems, optimizing forage allowance and grazing intensity may increase pasture productivity, reproductive performance, beef productivity, and possibly reduce GHG emissions. This study estimated GHG emissions per kg of live weight gain (LWG) and per h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 26 publications
(35 reference statements)
7
43
2
5
Order By: Relevance
“…We refer to these dates as Spring 1 (0 months after exclosures were established), Autumn 1 (6 months after exclosures were established), Spring 2 (12 months after exclosures were established), and Autumn 2 (18 months after exclosures were established). Cattle grazing continued in the grazed areas throughout the study; livestock (primarily Hereford cattle) were free to roam throughout the year and between forest and grassland habitats [while we do not have specific stocking rates for our sites, in general, stocking rates for beef cattle in Uruguay are 0.55 livestock units ha -1 (Becona et al 2014)]. …”
Section: Field Methodsmentioning
confidence: 99%
“…We refer to these dates as Spring 1 (0 months after exclosures were established), Autumn 1 (6 months after exclosures were established), Spring 2 (12 months after exclosures were established), and Autumn 2 (18 months after exclosures were established). Cattle grazing continued in the grazed areas throughout the study; livestock (primarily Hereford cattle) were free to roam throughout the year and between forest and grassland habitats [while we do not have specific stocking rates for our sites, in general, stocking rates for beef cattle in Uruguay are 0.55 livestock units ha -1 (Becona et al 2014)]. …”
Section: Field Methodsmentioning
confidence: 99%
“…The use of different management practices has shown that there is great potential to reduce greenhouse gases (GHG) emissions produced by livestock, through improved grazing management (Becoña et al, 2014). Recently, new management technologies of forage allowance in rangeland have shown promising results in beef production per unit area (Soca et al, 2013), but the impact on relevant environmental variables such as methane emissions (CH 4 ) has not been quantified yet.…”
Section: Introductionmentioning
confidence: 99%
“…Data for an average, pasture-based farm in Uruguay were adopted from Becoña et al (2014). Cattle grazed natural pasture year-round, and concentrate supplementation was negligible (Becoña et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Cattle grazed natural pasture year-round, and concentrate supplementation was negligible (Becoña et al, 2014). The cattle breed was not mentioned explicitly for farms in Uruguay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation